Вплив античного світу на ойконімні утворення Галії / Influence of the Ancient World on the Formation of Place Names of Gaul - Рак Олександр (Актуальні питання суспільних наук та історії медицини, 2014)
Rak Oleksandr. Influence of the Ancient World on the Formation of Place Names of Gaul. Resume: The present paper traces the influence of such powerful classical civilizations as ancient Greece and Rome on the formation of Galician place names at the base of a linguistic and historical overview of the ancient epochs. Key words: toponym, place name, Greece, Rome, Gaul, Celts. Rak Oleksandr. Influence du monde antique sur la formation des noms de lieu de la Gaule. Résumé. Cet article retrace l'influence des puissants civilisations classiques de la Grèce antique et de la Rome sur la formation des noms de lieu galiciens à la base d’un aperçu linguistiques et historiques dans l’ancienne époque. Mots-clés: toponyme, nom de lieu, Grèce, Rome, Gaule, celtes. Рак Александр. Влияние античного мира на ойконимные образования Галлии. Резюме: В данной статье прослежено влияние мощных классических цивилизаций античной Греции и Рима на Галицкие ойконимные образования на основании лингвистического и исторического экскурсов в древние эпохи. Ключевые слова: топоним, ойконим, Греция, Рим, Галлия, кельты.